The Influence of Spiritual, Emotional, and Intellectual Intelligence on Work Performance at British Propolis Indonesia Partners - Nursyamsi; Rajindra; Farid; Henni Mande (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2024)
This research aims to determine and analyze the influence of spiritual, emotional and intellectual intelligence on work performance in British Propolis partners. The population in this study were all official British Propolis partners in the city of Palu. The number of samples used in this research was 60 respondents. This type of research is explanatory research which explains the causal relationship or influence between the dependent variable and the independent variable. The research instrument used was the gform questionnaire. Data testing was carried out with SPSS 21.0. The results of the research show that the spiritual intelligence variable has a positive and significant influence on work performance of British Propolis partners in the city of Palu with a calculated t value of 3.669, a sig-t value of 0.001. Furthermore, the emotional intelligence variable has a positive and significant influence on work performance of British Propolis partners in the city of Palu with a calculated t value of 3.737, a sig-t value of 0.000. The intellectual intelligence variable also has a positive and significant influence on work performance of British Propolis partners in the city of Palu with a calculated t value of 2.004, sig-t value of 0.050. Simultaneously, there is an influence of spiritual, emotional and intellectual intelligence on work performance in British Propolis partners in the city of Palu with a calculated F value of 27.964 which is greater than the F table which is 2.766 with a sig-F value of 0.000, which means that the analysis results show all the hypotheses. submitted in this research is accepted.